Adaptasi Komunikasi Migran Dalam Menghadapi Culture Shock - Putri Tina Anriana; Aswar Tahir (Indo Publishing, 2026)
This study aims to examine the communication adaptation of migrant workers in dealing with culture shock among female migrant workers from Olat Rawa Village, Moyo Hilir District, Sumbawa Regency. Differences in language, culture, social norms, values, and communication patterns in the destination country create various challenges that require migrant workers to adapt to a new social and cultural environment. This study employed a qualitative descriptive research design. Data were collected through in-depth interviews, observation, and documentation involving eight female migrant workers selected using a purposive sampling technique. The data were analyzed through the processes of data reduction, data display, and conclusion drawing, while the validity of the findings was ensured through source triangulation. The findings reveal that the participants experienced four stages of culture shock, namely the honeymoon, crisis, disorientation, and adjustment and recovery phases. During the honeymoon phase, the participants showed enthusiasm, curiosity, and optimism toward their new environment. In the crisis phase, they encountered communication barriers, cultural differences, emotional stress, work-related difficulties, and homesickness. During the disorientation phase, they experienced confusion in understanding the local language, social norms, customs, and communication patterns. In the adjustment and recovery phase, the participants gradually adapted by improving their verbal and nonverbal communication skills, learning the local language, using translation applications, and building positive relationships with employers and coworkers. The study concludes that communication competence, work experience, and environmental support play significant roles in helping migrant workers overcome culture shock, communicate effectively, and successfully adapt to a new cultural environment.